Lamina-associated polypeptide 2 (LAP2) expression patterns in transformed and cancer cells - Ward, Michelle Claire (Division of Medical Biochemistry, 2014)
The Lamina-associated polypeptide two (LAP2) proteins comprising three human isoforms, LAP2 +- LAP2Î² and LAP2 have been shown to provide a structural framework in the nucleus and to facilitate nuclear assembly and disassembly during the cell cycle. Expression profiling studies, using microarrays, identified elevated levels of LAP2Î± in cervical cancer patient material compared to normal. Altered expression of LAP2 may thus have significance in the development of certain cancers. The aim of this project was thus to independently confirm the up-regulation of LAP2Î± in cancer material and to determine the effect of inhibiting its expression on the biology of cancer and transformed cells. LAP2Î± mRNA and protein expression was shown to be elevated in cervical cancer tissue compared to normal cervical tissue by Real-time RT-PCR and immunohistochemical analysis respectively. Interestingly, LAP2 (both the LAP2Î± and LAP2Î² isoforms) was shown to be overexpressed in cervical cancer cell lines compared to a normal primary cervical epithelial cell line. Higher LAP2 expression appears to associate with cellular transformation as increased expression was observed in transformed human fibroblast cells compared to normal fibroblasts. LAP2 expression was also elevated in oesophageal cancer cell lines compared to normal suggesting that the overexpression of LAP2 associates with multiple cancer types. In order to determine the role of LAP2 in cancer cell biology, its expression was inhibited using specific siRNA molecules. Inhibition of LAP2 did not have an effect on adherent cell proliferation; however under anchorage-independent growth conditions a significant decrease in cell proliferation and colony formation was observed in LAP2 knockdown cells. This was accompanied by a decrease in cyclin D1 levels and an increase in p16 levels in LAP2 siRNA transfected cells. Our results did not conclusively show xiii that this decrease in proliferation was as a result of an alteration in the cell cycle profile or due to an increase in apoptosis. In addition, inhibition of LAP2 expression resulted in a decrease in Rb protein expression. It is proposed that LAP2 plays a role in stabilizing the Rb protein, as inhibition of LAP2 expression did not affect Rb mRNA levels but substantially reduced the protein half-life. In summary, increased LAP2 expression associates with transformed and cancer cells and suggests potential for use as a cancer biomarker. Its potential as an anti-cancer therapeutic, however requires further investigation.